Durational aspects of tautosyllabic vowel nasalization in (Brazilian) Portuguese: An airflow investigation. (11th May 2021) - Rothe-Neves, Rui
Abstract : This study investigates coarticulatory effects caused by the following consonant – either a stop or a fricative – on the duration of the oral and the nasalized portion of the nasal vowel and the nasal murmur in sequences within Portuguese words like tensa [ˈtẽsɐ] 'tense' versus tenta [ˈtẽtɐ] '(s/he) tries.' The results replicate previous observations that duration adjustments affect the vowel's nasalized portion, as is the case for languages in which the speaker intends nasalization. The second hypothesis is that adjustments in duration as a function of the following onset do not affect the nasalization duration, but only the timing of a nasal gesture relatively constant in duration. Results show that irrespective of the following consonant ([s] or [t]), nasalization remains constant in duration. However, a shorter nasal murmur or a more extended postnasal consonantal oral portion does not follow more extended vowel nasalization. As the entire VNC sequence increases on an individual basis, so does the nasalization. Still, increasing nasalization comes at a cost for the duration of the oral part of the vowel irrespective of [s, t]. These results are compatible with that speaking rate influences coordination timing between the beginning of the vowel and the beginning of nasalization.